Volunteer Health Service in COVID-19 Prevention at Exit Toll Leces Probolinggo - Mellya Puspitasari; Zainal Munir (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This abstract discusses the role of healthcare volunteers in COVID-19 prevention alongside government actions like Community Activity Restrictions (PPKM) at Exit Toll Leces Probolinggo. Method: The study describes the stages of restriction and prevention activities, including assemblies, checkpoints, temperature checks, and antigen swab tests, as measures to enforce health protocols and policies among the public. Practical Applications: The findings demonstrate that the public continues to adhere to health protocols and policies, such as mask-wearing, vaccination, and obtaining negative swab test results for travelers from July 12 to July 16, 2021. This underscores the importance of community engagement in combating Covid-19. Conclusion: This research underscores the valuable role of volunteers in COVID-19 prevention, alongside government efforts to implement restrictions and health protocols. The study's insights contribute to our understanding of effective pandemic management strategies.